Cities Coping with COVID-19: - Simon, David; Arano, Angeles; Cammisa, Mariana; Perry, Beth; Pettersson, Sara; Valencia, Sandra; Oloko, Michael; Sharma, Tarun; Vora, Yutika; Smit, Warren; Riise, Jan (Tylor and Francis Group, 2021)
This Symposium represents an experimental format within CITY, as the latest part of the relaunched journal’s efforts to diversify its contents and attract new readers, especially among communities of practice engaged in urban governance, policy and practice. As such, it provides rapid publication of insights intended to inform ongoing debate and crisis responses as cities everywhere grapple with the profound consequences of the pandemic and its implications for so many facets of urban ‘business as usual’.For the final four years of its existence, Mistra Urban Futures, the leading international research centre on urban sustainability, based in Gothenburg, Sweden, pioneered the extension of its renowned transdisciplinary co-creation/co-production methods to cross-city comparative research embracing up to seven diverse cities in different world regions (Simon, Palmer, and Riise 2020). These cities are Gothenburg and Malmö in Sweden, Sheffield and Greater Manchester in the UK, Cape Town in South Africa, Kisumu in Kenya, Buenos Aires in Argentina and Shimla in northern India. Although the experimental research projects formally ended in December 2019, 2020 was a consolidation year with continuation funding from the Swedish International Development Cooperation Agency (Sida) to maximise outputs and other added value through dissemination and engagement with global agendas.The largest experimental project utilised transdisciplinary co-production methods to examine how seven diverse cities on four continents responded to and engaged with the 2015–16 global sustainable development agenda, comprising especially Sustainable Development Goal (SDG) 11 and the New Urban Agenda (NUA). These comprise the specifically urban components of the global agenda, providing aspirational commitments, goals, targets and indicators to promote urban sustainability with equity – expressed as ‘leaving no-one behind’. Responses from the cities were diverse, ranging from low engagement because of a lack of guidance from national government and because existing local indicators were deemed adequate (Sheffield) to enthusiasm to enhance engagement with national government and in order to align activities and reporting to global indicators (Cape Town) and a valuable opportunity to update, rethink and systematise service delivery and public investment priorities (Kisumu) (Simon et al. 2016; Valencia et al. 2019, 2020). The 17 SDGs (Figure 1) have a 15-year lifespan (2016-2030) and were designed as more comprehensive and integrated successors to the eight Millennium Development Goals (MDGs), which ran from 2001-2015. Each Goal comprises a set of targets, which in turn have one or more indicators against which progress is to be measured annually or some other interval. In contrast to the rapid, top-down way in which the MDGs had been conceived and imposed on low- and middle-income countries, the SDGs were designed through a broad, global and remarkably inclusive process of consultation and negotiation over three years and apply to all countries. The UN statistical unit in the Division of Economic and Social Affairs (UN-DESA) has ultimate responsibility and undertakes ongoing monitoring and revisions in the light of feedback received, including from the Mistra Urban Futures projects. The NUA underwent a similar formative process, and is a broad, visioning and aspirational document, in part because the originally intended direct link to the SDGs as its monitoring and evaluation framework was not politically acceptable to many national governments. Naturally, the framing of both Agenda 2030 and the NUA, and the choices of SDG targets and indicators, were contested and ultimately represent trade-offs between optimality, practicability within constraints of widespread data availability (so that most cities and countries can report on them) and the resource implications of implementation, and political acceptability to UN member states. These issues are explored in a growing critical literature that evaluates various aspects of the 2030 agenda and of individual goals, targets and indicators, including practicability, cost effectiveness, risks of selective cherry picking to use the progress reviews instrumentally for political expediency rather than as a mechanism to drive substantive progressive change, and hence the likely effectiveness of the SDGs overall as a means to drive substantive change (e.g. Arfvidsson et al. 2017; Barnett and Parnell 2016; Garschagen et al. 2018; Hansson, Simon, and Arfvidsson 2019; Klopp and Petretta 2017; McGranahan, Schensul, and Singh 2016; Parnell 2016; Patel et al. 2017; Rudd et al. 2018; Sánchez Gassen, Penje, and Slätmo 2018; Simon et al. 2016; Sustainable Development Solutions Network 2020; Valencia et al. 2019, 2020).
Comparative Perspectives